A Critical Review on the Trend of Integrated Reporting Capitals - Jaya Kumar Shanmugam; Duruvendran Jayakanthan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This paper analyzes the trend of Integrated Reporting capitals in Malaysia, by introducing of integrated reporting framework on the 6 capitals and comparison with some countries across the continent. This research analyses the depth and breadth of IR capital reporting using a checklist derived from the IIRC's framework and conducted using content analysis. The analysis shows that IR capitals are becoming much more forthcoming with information as Financial capital, Manufacture capital, Intellectual capital, Human capital, Social and Relation capital, and Natural capital are all shown to have significantly increased in the sampled IRs. This study particularized each capital on its definition, purpose, and disclosures and help people in charge of governance keep an eye on how they're reporting on IR capitals. It's useful since it highlights where IR capitals may stand to enhance their level of disclosure. This would then aid in assessing whether or not the framework itself needs to be revised